Numerical simulation and experimental validation of inverted planar perovskite solar cells based on NiOx hole transport layer. (December 2017) - Wei, Xiaoqing; Wang, Xian; Jiang, Hailong; Huang, Yongliang; Han, Anjun; Gao, Qi; Bian, Jiantao; Liu, Zhengxin
Abstract: Numerical simulation of inverted planar perovskite solar cells based on NiOx hole transport layer was performed with AMPS-1D program. The simulated device parameters were shown to agree well with our experimental work. The simulated results revealed that the device contained typical p-i-n junction configuration. The optimum thickness of the absorber, the effects of the absorber quality, the defect density of interfaces, the effects of VBO and CBO, the interface contact at front and back electrodes were analyzed. Open-circuit voltage mainly depended on the defect density in CH3 NH3 PbI3 layer, the recombination at HTL/CH3 NH3 PbI3 and ETL/CH3 NH3 PbI3 interface, the values of VBO and CBO, while short-circuit current mainly depended on the thickness of CH3 NH3 PbI3 layer. Fill factor was significantly influenced by the interface contact at front and back electrodes. Remarkably, a power conversion efficiency of 21.8% is obtained under optimised conditions. Real devices with PCE of up to 15% were obtained by initially optimizing the preparation of CH3 NH3 PbI3 absorber layer. Our work can provide some important guidance for device design and optimization from the considerations of both theory and experiment. Highlights: Electrostatics and J-V characteristic of perovskite solar cells are analyzed. The optimised VBO of perovskite/HTM and CBO of perovskite/ETM are both 0 eV. Real devices with PCE of up to 15% and simulated devices with PCE of 21.8% are obtained.